Chicano Communists and the Struggle for Social Justice - Buelna, Enrique M. (Book collections on Project MUSE., 2019)
In the 1930s and 1940s the early roots of the Chicano Movement took shape. Activists like Jesús Cruz, and later Ralph Cuarón, sought justice for miserable working conditions and the poor treatment of Mexican Americans and immigrants through protests and sit-ins. Lesser known is the influence that Communism and socialism had on the early roots of the Chicano Movement, a legacy that continues today. Examining the role of Mexican American working-class and radical labor activism in American history, Enrique M. Buelna focuses on the work of the radical Left, particularly the Communist Party (CP) USA. Buelna delves into the experiences of Cuarón, in particular, as well as those of his family. He writes about the family's migration from Mexico; work in the mines in Morenci, Arizona; move to Los Angeles during the Great Depression; service in World War II; and experiences during the Cold War as a background to exploring the experiences of many Mexican Americans during this time period. The author follows the thread of radical activism and the depth of its influence on Mexican Americans struggling to achieve social justice and equality. The legacy of Cuarón and his comrades is significant to the Chicano Movement and in understanding the development of the labor and civil rights movements in the United States. Their contributions, in particular during the 1960s and 1970s, informed a new generation to demand an end to the Vietnam War and to expose educational inequality, poverty, civil rights abuses, and police brutality.